Pengaruh Penggunaan Multimedia Wordwall Terhadap Hasil Belajar PAI di SMP Muhammadiyah 1 Medan - Yuliyani, Yuliyani; Mahariah, Mahariah (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the effect of the use of Wordwall multimedia on the learning outcomes of Islamic Religious Education (PAI) Khulafaur Rasyidin material in Integrated VII grade students at SMP Muhammadiyah 1 Medan. The method used is quantitative with a quasi-experimental approach, using a pretest-posttest design in the experimental group given learning with Wordwall multimedia and the control group with conventional media, namely Al-Islam books with a sample of 60 students. The research instrument was a 20-item multiple choice test that had been declared valid and reliable. Data analysis began with descriptive test, Shapiro-Wilk normality test, and Levene homogeneity test, which showed that the posttest data were not normally distributed and the variances were not uniform. Therefore, the Mann-Whitney U nonparametric test was used to test the hypothesis at a significance level of α = 0.05. The results showed that the use of Wordwall multimedia significantly improved students' learning outcomes. The average posttest score of the experimental group, which used Wordwall-based learning, increased from 67.17 to 88.00, showing a substantial improvement. In contrast, the control group that received conventional learning only increased from 57.50 to 71.00. Analysis using the Mann-Whitney U test revealed a U value of 232.50 and Z of -3.241, with p = 0.001. This shows that the difference in the improvement of learning outcomes between the two groups is significant (p < 0.05). With the mean rank of the experimental group's posttest reaching 37.75, much higher than the control group which was only 23.25, it can be concluded that Wordwall multimedia has a significant positive impact on Islamic Religious Education learning outcomes at SMP Muhammadiyah 1 Medan. The implication of this result shows that the application of technology in learning can improve the understanding of important concepts in Islamic education.